Behavioral Assumptions of Management Accounting – Report of a Field of Study. - Caplan, Edwin H. (The Accounting Review, 1968)
It is generally suggested by the accounting professionals that the principal objective of management accounting is the influencing of behavior. And in order to accomplish this objective, the management accountant must function with some view of human behavior in mind. The article considers two cases of formalizing the views of behavior into model which could be used for testing the validity and relevance of the accountant's behavioral assumptions. The first of these is termed the traditional management accounting view. The second theoretical model which was considered is not usually associated with either the literature or educational processes of management accounting. Each of these models is based on a set of underlying assumptions about human behavior, and it is these assumptions which determine the character of the model itself. The findings of this field study appear to suggest that many management accountants tend toward a traditional view of behavior and they are not alone in this respect.